In vivo screening antifungal activity of methanolic extract of Protoparmeliopsis muralis against Aspergillus flavus - Somaye Rashki; Tahereh Valadbeigi (Fasa University of Medical Sciences, 2017)
Background & Objective: Lichens are the result of the symbiosis of fungi and algae or a cyanobacterium. Various biological activities of some lichen and their components such as: antifungal, anti-bacterial, anti-tumor, anti-inflammatory, antiprotozoal substances are known. In the present study, antifungal activity of methanolic extract of Protoparmeliopsis muralis against Aspergillus flavus is investigated on rats. Materials & Methods: 500 g of Protoparmeliopsis muralis was collected from KaneGonbad mountains in Ilam province, the methanol extract was prepared by soxhle. In order to determine the antifungal activity in in vivo conditions, a wound was created and infected with Aspergillus flavus. Having infected the wound, the researchers divided the rats into 4 subgroups: negative control group, treated with Kotrimoksazol, %5 ointment extract methanolic P. muralis, and with %10 ointment extract methanolic P. muralis. Treatment continued until complete healing of the wound. Finally, the percentage of wound healing was calculated. Results: The result of the present study demonstrated that methanolic extract of P. muralis decreased the area of wound in the treatment group compared to the control group. Conclusion: The antifungal and antioxidant activity of the extract of Protoparmeliopsis muralis accelerated the wound healing process.